Life Sciences, Medicine and Biomedicine – supporting open access publishing - Editorial (Life Sciences, Medicine and Biomedicine, 2024)
As an open access journal, Life Sciences, Medicine and Biomedicine (LSMB) has made remarkable progress. LSMB is currently indexed by MyJurnal, the Directory of Open Access Journals (DOAJ), the Malaysian Citation Index (MyCite) and Scilit. Data shows that a vast majority of articles published since 2017 are seeing growth in the number of citations, indicating that these articles are visible and gaining readership. One of the key elements for the journal’s success is the rigorous peer-review process. A step-by-step authors guide for manuscript preparation and submission, followed by a systematic peer-review process ensures a seamless yet efficient system. Beginning July 2021, all submitted manuscripts are processed through similarity checks before being approved for peer-review. This is in addition to other compliance checks related to publication ethics and best practices of the journal in line with the globally accepted recommendations. As part of the journal’s contributorship policy, authors are required to declare contributions of each person named in the manuscript. In light of recent development in generative artificial intelligence, authors are also required to confirm that all submitted work including texts, figures and images are not created using generative AI. Importantly, the dedication and commitment of all the editors, associate editors and reviewers were instrumental in ensuring conformity to the benchmark and standards required by the journal. Since the establishment of the journal in 2017 and looking forward beyond 2024 – these areas of quality assurance will remain the fundamental focus of Life Sciences, Medicine and Biomedicine. In recent years, the journal has seen growing publications from diverse geographical locations including authors from Indonesia, Japan, Malaysia, Nigeria, Philippines, Thailand, United Kingdom, and the United States. To further support this growth, the journal is continuously engaging subject matter experts in different areas of life sciences, medicine and biomedicine for editorial roles. Currently, the editorial and International Advisory Board members include experts from Australia, Bangladesh, China, Indonesia, Iraq, Japan, Malaysia, Pakistan, Philippines, Singapore and the UK, coming from more than 15 different research and higher education institutions. As the journal continues to reach an ever-growing audience, a variety of solutions are being explored to make scientific publishing readily accessible to everyone, the authors, researchers, and the public. Work is in progress to support authors when needed. This is to ensure that publishing cost will not be an obstacle for sharing scientific discoveries if, and when manuscripts are accepted for publication after peer-review. Mechanisms are being developed to allow the journal to address this on a case-by-case basis. The journal is fully committed towards open access allowing authors to retain the copyright of their published work and to provide the public unlimited access to these resources, within the scope of the open access policies. The journal welcomes manuscript submissions for articles in a few categories including research article, review, mini review, case report and opinion pieces. It is hoped that through these open access publications, broader conversations will emerge between researchers around the world. With the comprehensive framework in place, and the current trajectory, the journal is looking forward to establishing its presence as a rigorous, credible and reputable peer-reviewed open access journal in the region and globally.